Protection of microgrids using differential relays - Dewadasa, M.; Ghosh, Arindam; Ledwich, G. (Institute of Electrical and Electronics Engineers ( IEEE ), 2011)
A microgrid provides economical and reliable power to customers by integrating distributed resources more effectively. Islanded operation enables a continuous power supply for loads during a major grid disturbance. Reliability of a microgrid can be further increased by forming a mesh configuration. However, the protection of mesh microgrids is a challenging task. In this paper, protection schemes are discussed using current differential protection of a microgrid. The protection challenges associated with bi-directional power flow, meshed configuration, changing fault current level due to intermittent nature of DGs and reduced fault current level in an islanded mode are considered in proposing the protection solutions. Relay setting criterion and current transformer (CT) selection guidelines are also discussed. The results are verified using MATLAB calculations and PSCAD simulations.